Records of the U.S. Department of State relating to the internal affairs of Korea, 1940-1944 : Department of State decimal file 895 (1940)
Typescript and holograph reports and correspondence of the State Dept. relating to the internal affairs of Korea, 1940-1944. Enclosures include newspaper clippings, etc.